Methylglyoxal is associated with changes in kidney function among individuals with screen‐detected Type 2 diabetes mellitus. Issue 12 (25th August 2016) - Jensen, T. M.; Vistisen, D.; Fleming, T.; Nawroth, P. P.; Rossing, P.; Jørgensen, M. E.; Lauritzen, T.; Sandbæk, A.; Witte, D. R.
Abstract: Aims: The glycolysis‐derived metabolite methylglyoxal has been linked to clinical microvascular complications, including diabetic nephropathy. We aimed to further investigate the hypothesis that methylglyoxal is involved in decline in renal function by assessing the associations between measures of renal function during a 6‐year follow‐up in 1481 people with screen‐detected Type 2 diabetes, as part of the Danish arm of the ADDITION‐Europe trial (ADDITION‐DK). Methods: Biobank serum samples collected at ADDITION‐DK baseline (2001–2006) and follow‐up (2009–2010) were used in the current analysis of methylglyoxal. We assessed cross‐sectional baseline and longitudinal associations between methylglyoxal and urinary albumin‐to‐creatinine ratio (ACR) or estimated GFR (eGFR), and between methylglyoxal and categories of albuminuria or reduced eGFR. Results: Baseline methylglyoxal was positively associated with ACR at baseline (12% higher ACR per doubling in methylglyoxal levels), and change in methylglyoxal during 6 years of follow‐up was inversely associated with change in eGFR (–1.6 ml/min/1.73 m 2 per doubling in methylglyoxal change), in models adjusted for age, sex, HbA1c, systolic blood pressure, anti‐hypertensive treatment, LDL‐cholesterol, lipid‐lowering treatment, C‐reactive protein and smoking. Conclusions: In a population of people with screen‐detected Type 2 diabetes, we observed associations between methylglyoxal and markers of renal function: 6‐year change in methylglyoxal was inversely associated with 6‐year change in eGFR. Also, methylglyoxal at baseline was positively associated with ACR at baseline. Our study lends further support to a role for methylglyoxal in the pathogenesis of diabetic nephropathy. What's new?: In this study, the glucose‐derived metabolite methylglyoxal was found to be associated with changes in kidney function. This is one of the largest studies with methylglyoxal data ( n ˜ 1400) obtained within a clinical setting (well‐characterized population of people with screen‐detected Type 2 diabetes mellitus). Measurements of serum methylglyoxal were performed in samples from two time points (6 years of follow‐up). The findings lend support to existing research implicating methylglyoxal in microvascular diabetes complications.